The Usborne introduction to genes & DNA - Claybourne, Anna.; Moncrieff, Stephen (Tulsa, Okla. : EDC, 2006)
An illustrated introduction to genes and DNA, explaining what they are and how they work, and discussing heredity, the history of discovery in the field, modern gene science, and ethical concerns. Includes a time line and other reference tools, including related Web site addresses.
"Internet-linked"--Cover.
Includes index.
6.8
3-6
Keywords: DNA -- Juvenile literature; Genes -- Juvenile literature; Genetics -- Juvenile literature; DNA; Genes; Genetics; DNA; Genetics